OPTIMALISASI KREATIVITASOPTIMALISASI KREATIVITAS SISWA BERBASIS PROGRAM SEKOLAH ADIWIYATA DI SEKOLAH DASAR SISWA BERBASIS PROGRAM SEKOLAH ADIWIYATA DI SEKOLAH DASAR - Ummisyia Shabira; Achmad Fathoni (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
The Adiwiyata program plays a strategic role in fostering awareness of the declining environmental conditions. This research aims to explore the optimization of student creativity based on the Adiwiyata School Program at Elementary School (SDN) 11 Sondakan, Surakarta. The research method used is qualitative research with a descriptive approach. Data were collected through interviews, observations, and documentation. Interview results were obtained from teachers, students, and the school principal conducted from August to November 2023, observing Adiwiyata program activities, and documenting related Adiwiyata activities. The validity of the data used the source triangulation technique, with an interactive model of data analysis consisting of data reduction, data display, and conclusion drawing. The research results show that the Adiwiyata program at SDN 11 Sondakan has a positive impact, evident in waste management, creative student activities, and school greening. The implications of this research can be used as a model for Adiwiyata implementation to enhance student creativity and environmental awareness in elementary schools